Factors Related to Cardiovascular Disease Risk Reduction in Midlife and Older Women: A Qualitative Study - Sara C. Folta, PhD; Jeanne P. Goldberg, PhD; Alice H. Lichtenstein, DSc; Rebecca Seguin, MS; Peter N. Reed, MPH; Miriam E. Nelson, PhD (Centers for Disease Control and Prevention, 2008)
IntroductionCardiovascular disease (CVD) is the leading cause of death for women in the United States. A healthy diet and appropriate physical activity can help reduce the risk for CVD. However, many women do not follow recommendations for these behaviors. In this study, we used qualitative methods to better understand knowledge and awareness about CVD in women, perceived threat of CVD, barriers to heart-healthy eating and physical activity, and intervention strategies for behavior change.MethodsWe conducted four focus groups with 38 white women aged 40 years or older in Kansas and Arkansas. We also interviewed 25 Cooperative State Research, Education, and Extension Service agents in those states. Environmental audits of grocery stores and the physical environment were done in three communities.ResultsMost women were aware of the modifiable risk factors for CVD. Although they realized they were susceptible, they thought CVD was something they could overcome. Common barriers to achieving a heart-healthy diet included time and concern about wasting food. Most women had positive attitudes toward physical activity and reported exercising in the past, but found it difficult to resume when their routine was disrupted. The environmental audits suggested that there are opportunities to be physically active and that with the exception of fresh fish in Kansas, healthful foods are readily available in local food stores.ConclusionInterventions to change behavior should be hands-on, have a goal-setting component, and include opportunities for social interaction. It is especially important to offer interventions as awareness increases and women seek opportunities to build skills to change behavior.